Investigation of structural, hardness, adhesion, and tribological properties of CrN and AlCrN coatings deposited on cylinder liner - Semih Mahmut Aktarer; Yaşar Sert; Tevfik Küçükömeroğlu (Materials & Design)
Friction between cylinder liners and piston rings is one of the major energy losses in engines. Minimizing this friction reduces fuel consumption, lowers emissions, and enhances performance. To address this, CrN and AlCrN coatings were applied to grey cast iron (GCI) cylinder liners using cathodic arc deposition method. Their tribological properties were evaluated under varying loads through reciprocating wear tests in dry and lubricated conditions. The structure of the coatings was characterized by electron microscopy (SEM-EDS) and X-ray diffraction (XRD), while the hardness and adhesion properties were characterized by nanoindentation and scratch testing. The CrN coating showed 21% lower hardness but 18% higher adhesion strength and superior crack resistance compared to AlCrN. In dry, low-load conditions, AlCrN’s higher hardness resulted in 30% better wear resistance. However, under high-load conditions, the wear resistance of CrN coating is about 3 times higher than AlCrN coating due to its improved adhesion properties. CrN and AlCrN coatings reduced wear rates by approximately 70 and 24 times, respectively, compared to GCI. In lubricated conditions, CrN’s wear rate was 5.3 times lower than GCI and 2.4 times lower than AlCrN. These findings show that AlCrN is ideal under low loads, while CrN is better for high-loads.